PENGARUH MOTIVASI DAN DISIPLIN GURU TERHADAP KINERJA GURU DI SMPN 8 KOTA KEDIRI - Siti Nurwasiyah (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This study aims to determine: (1) The effect of work motivation on the performance of teachers in the country eight Smp Kediri, (2) Effect of labor discipline on the performance of teachers in the country eight Smp Kediri, (3) Effect of motivation and discipline of work jointly the performance of teachers in the country Smp kediri.Penelitian eight cities including quantitative research and using statistical analysis infersial. The population in this study are all teachers Smp Kediri eight countries totaling 37 people guru.Teknik sampling was census. The instrument used in this study is a questionnaire that is used to reveal the variable data research work motivation, work discipline, and performance data analysis used guru.Teknik is Test Test linearity and multicollinearity. The results of the study are: (1) Work Motivation simultaneously and partially significant positive effect on the performance of teachers in the country eight Smp Kediri. (2) Discipline simultaneously work significantly and positively related to the performance of teachers in the country eight Smp Kediri. (3) Motivation and discipline are simultaneous and significant positive effect on the performance of teachers in the country eight Smp Kediri. Keywords: Motivation, Discipline, Performance teachers